2022
DOI: 10.1155/2022/7667770
|View full text |Cite|
|
Sign up to set email alerts
|

Paeoniflorin Protects H9c2 Cardiomyocytes against Hypoxia/Reoxygenation Induced Injury via Regulating the AMPK/Nrf2 Signaling Pathway

Abstract: Myocardial ischemia/reperfusion (MIR) injury contributes to the exacerbation of heart disease by causing cardiac arrhythmias, myocardial infarction, and even sudden death. Studies have found that paeoniflorin (PF) has a protective effect on coronary artery disease (CAD). However, the mechanism of PF in MIR has not been fully investigated. The purpose of this study was to investigate the functional role of PF in H9c2 cells subjected to hypoxia/reoxygenation (H/R). Here, PF treatment enhanced cell viability in H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%